Rediseño del proceso de atención para disminuir la cola en el restaurante "La Casa del Plaza" (2021)
La Casa del Plaza is one of the restaurants located in the DuNord Plaza at Universidad del Norte, dedicated mainly to the sale of ordinary food. This restaurant has a high demand at lunchtime, presenting, most of the time, a queue of approximately 20 people and waiting times of about 30 minutes. Given this situation, this project proposed to redesign the restaurant's customer service process in order to reduce the number of people in the queue to a maximum of 15 and to reduce the waiting time to a maximum of 20 minutes. For this purpose, historical data provided by DuNord and information collected in a sample taken by the authors were used. Then, a demand forecast was made for the second half of 2021, taking into account the pandemic situation. Based on this projection and the queuing theory, an analysis was made of the number of servers required, according to the service times obtained. Likewise, a study of the spatial distribution of the queue generated by the service at the cash register and a simulation of the current situation were carried out. Two alternative solutions were proposed: the first, to add a new payment point, and the second, to divide the line or group it according to the type of diner; that is, to make a distinction between those willing to pay at the cash register and those diners who will not use it because of a previous payment. As a result, based on an improved proposal of the plant layout, explained through a graphic analysis and a simulation model in Arena, the second alternative was chosen as the final proposal, where a 69% decrease in waiting times and a 65% decrease in the number of people in line was obtained.